Experimental Study of the Performance of Turbo-Charged Gasoline Direct-Injection Engine Based on Different Pre-Chamber Structures - Xiaowei Zhao; Yuedong Sun; Zhendong Zhang; Congbo Yin (Energies, 2024)
In this paper, in order to improve the fuel economy of the actual application of the engine under multi-operating conditions, an experimental study is carried out on a turbo-charged direct-injection engine based on different pre-chamber structures. The engine used for the study is a four-cylinder turbo-charged direct-injection gasoline engine with different structures of pre-chamber spark plugs. The operating conditions in this study include load characteristics at 2000 r/min and characteristic loads at different speeds, including 3000 r/min, 3200 r/min, and 3600 r/min. With stable BMEP or fully open throttle and pedal, the experiment was conducted by the spark angle scanning method to collect data of engine power, economy, and emission under each condition. It was found that the pre-chamber structure has a direct effect on engine performance, with a clear load demarcation line for its effect. Under the WOT condition, the power of pre-chamber ignition is 1.6% higher than that of conventional spark plugs; at the low load of 2 bar, the economy of pre-chamber ignition is degraded by 6%; at the medium load of 8 bar, the economy of the two is comparable; at the large load of 16 bar, the fuel economy proves advantageous. Compared with conventional spark plugs, the pre-chamber spark angle can be advanced by 2~3 °CA, and the pre-chamber ignition with separate ground electrodes is highly reliable. The emission levels of the pre-chamber spark plugs and conventional spark plugs are comparable at all loads.